MI-CO (MILLENNIAL COOPERATIVE): SOLUSI REBRANDING KOPERASI ERA MILENIAL MENYONGSONG BONUS DEMOGRAFI 2030 - Kevin Michael Kristian; Aisyah Nurush, shoba; anggun, anggun; Feryanto, Feryanto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
Cooperatives are institutions that are expected to become pillars or pillars of the nationaleconomy and as an institution of the people's economic movement, where members are themain force possessed by cooperatives. Cooperatives have many advantages when comparedto corporations or other business entities, including being able to create economies of scalebecause cooperatives can produce more output with lower average costs and are able tocompete because cooperatives can create bargaining positions. Being a member of acooperative will be very beneficial if seen from the advantages possessed by the cooperative.In addition to the considerable potential of cooperatives, cooperatives also face challenges intheir development. The challenges for cooperatives are increasingly supported because todaywe are in the Industrial 4.0 era. The cause of the many challenges faced by cooperatives isbecause of the lifestyle changes of millennials that are so fast and uncertain (disruptive), dueto the rapid development of information technology, robotic, artificial intelligence,transportation, and communication. Survey conducted by researchers with 86 respondentswith an age range of 18-30 years, showed that the millennial generation considerscooperatives still relevant for now, which is 82.4% of 86 respondents stated cooperatives arestill relevant. This indicates that cooperatives are still very potential to be developed in thecurrent millennial era but rebranding is needed so that cooperatives can be accepted bymillennials. The rebranding can be carried out by making various innovations, one of whichis the Millennial Cooperative (Mi-Co) being a cooperative concept that is in accordance withthe principles, values, and identity of cooperatives in their operations as well as in accordancewith millennial characteristics.